2002
DOI: 10.1063/1.1436270
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation suppression in InGaN epitaxial layers due to biaxial strain

Abstract: Phase separation suppression due to external biaxial strain is observed in InxGa1−xN alloy layers by Raman scattering spectroscopy. The effect is taking place in thin epitaxial layers pseudomorphically grown by molecular-beam epitaxy on unstrained GaN(001) buffers. Ab initio calculations carried out for the alloy free energy predict and Raman measurements confirm that biaxial strain suppress the formation of phase-separated In-rich quantum dots in the InxGa1−xN layers. Since quantum dots are effective radiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 10 publications
3
66
1
Order By: Relevance
“…Quantum dot like-structures which were observed in relaxed c-InGaN layers and DHs [112,113] seem to be absent in fully strained c-InGaN/GaN QWs. This conclusion is in good agreement with recent investigations of strained and relaxed c-InGaN/GaN DHs grown on GaAs substrates which revealed that the formation of QD-like structures in InGaN is suppressed by strain in these layers [117].…”
Section: Cubic Ingan-layerssupporting
confidence: 90%
“…Quantum dot like-structures which were observed in relaxed c-InGaN layers and DHs [112,113] seem to be absent in fully strained c-InGaN/GaN QWs. This conclusion is in good agreement with recent investigations of strained and relaxed c-InGaN/GaN DHs grown on GaAs substrates which revealed that the formation of QD-like structures in InGaN is suppressed by strain in these layers [117].…”
Section: Cubic Ingan-layerssupporting
confidence: 90%
“…The generalized Ising Hamiltonian, or the energy expansion in terms of multisite interaction energies allows us to search for the ground state of In x Ga 1−x N , by comparing the energies of different structures at the same alloy composition x. The results can be summarized as follows: i) The biaxial strain induced by the GaN buffer suppresses the tendency of the alloy to phase separate and acts as the driving force to form ordered structures at certain stoichiometric compositions [14]. There are several ordered structures with energies close to the minimum, which leads to the conclusion that a mixture of ordered phases or domains of ordered phases with different In content may arise depending on the growth conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It has been argued that self-organized nanometer scale In-rich quantum dots (QDs), originated from In-segregation taking place in the In x Ga 1−x N alloys, are the source of a radiative recombination channel emitting in the blue-green region of the spectrum [10,11,12,13]. It was also shown that the effect of biaxial strain induced by a pseudomorphic growth process in InGaN leads to phase separation suppression effects [14]. In addition to the phase separation process, chemical ordering on the group-III sublattice of InGaN has been reported [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…15 On the other hand, it has been recognized from theory and experience for a long time that the critical temperature lowers significantly due to biaxial strain in coherently grown semiconductor epitaxial layers and the miscibility gap may even be suppressed. 16,17 However, for MS only few works studied and/or analyzed the stability and its relation with external biaxial strain. 7,18 Therefore, a deep understanding of the role played by strain on phase separation in GaMnAs and GaCrAs layers is highly desirable.…”
Section: Introductionmentioning
confidence: 99%